Loss of NLRP6 expression increases the severity of acute kidney injury - Valino-Rivas, Lara; Cuarental, Leticia; Nuñez, Gabriel; Sanz, Ana B; Ortiz, Alberto; Sanchez-Nino, María Dolores (Oxford University Press, 2025)
Background. Nlrp6 is a nucleotide-binding oligomerization domain-like receptor (NLR) that forms atypical inflamma somes. Nlrp6 modulates the gut epithelium interaction with the microbiota. However, the expression and function of Nlrp6 in the kidney, a sterile environment, have not been characterized. We explored the role of Nlrp6 in acute kidney injury (AKI). Methods. In a transcriptomics array of murine nephrotoxic AKI, Nlrp6 and Naip3 were the only significantly downregu lated NLR genes. The functional implications of Nlrp6 downre gulation were explored in mice and in cultured murine tubular cells. Results. Nlrp6 was expressed by healthy murine and human kidney tubular epithelium, and expression was reduced during human kidney injury or murine nephrotoxic AKI induced by cisplatin or a folic acid overdose. Genetic Nlrp6 deficiency resulted in upregulation of kidney extracellular signal¿regulated kinase 1/2 (ERK1/2) and p38 mitogen-activated protein kinase (MAPK) phosphorylation and more severe AKI and kidney in flammation. In cultured tubular cells, Nlrp6 downregulation in duced by specific small interfering RNA resulted in upregula tion of ERK1/2 and p38 phosphorylation and chemokine messenger RNA expression and downregulation of the nephro protective gene Klotho. MAPK inhibition prevented the inflam matory response in Nlrp6-deficient cells. Conclusion. Nlrp6 dampens sterile inflammation and has a nephroprotective role during nephrotoxic kidney injury through suppression of MAP kinase activation.